Theories of political economy - Caporaso, James A., 1941-; Levine, David P., 1948- (Cambridge : Cambridge University Press, 1992)
'Political economy' has been the term used for the past 300 years to express the interrelationship between the political and economic affairs of the state. In Theories of Political Economy, first published in 1992, James A. Caporaso and David P. Levine explore some of the more important frameworks for understanding the relationship between politics and economics, including the classical, Marxian, Keynesian, neoclassical, state-centred, power-centred, and justice-centred approaches. The book emphasises both the differences between these frameworks and the issues common to them.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: elektronické knihy; electronic books; Economics; Political science